Mycobacterium bovis naturally infected calves present a higher bacterial load and proinflammatory response than adult cattle - Carrisoza-Urbina, Jacobo; Bedolla-Alva, Mario A.; Hernández-Pando, Rogelio; López-Macías, Constantino; Huerta-Yepez, Sara; Baay-Guzmán, Guillermina; Juárez-Ramírez, Mireya; Gutiérrez-Pabello, José A. (Frontiers in Veterinary Science, 2023)
Granulomas are characteristic bovine tuberculosis lesions; studying this structure has improved our understanding of tuberculosis pathogenesis. However, the immune response that develops in granulomas of young cattle naturally infected with Mycobacterium bovis (M. bovis) has not been fully studied. Our previous work described an atypical pattern in granulomatous lesions of cattle younger than 4 months (calves) naturally infected previously M. bovis that did not correspond to the histological classification previously proposed. Histologically, granulomas from calves lack a connective tissue capsule and have fewer multinucleated giant cells (MGCs) and more acid-fast bacilli (AFB) than the classic tuberculosis lesions found in cattle older than 1 year (adults); this suggests a deficient immune response against M. bovis infection in young animals. Therefore, we used IHC and digital pathology analysis to characterize the in situ immune response of granulomas from young and adult cattle. The immunolabeling quantification showed that granulomas from calves had more mycobacteria, CD3+ cells, IFN-γ, TNF-α, and inducible nitric oxide synthase (iNOS) than those of adult cattle. Furthermore, calf granulomas showed lower immunolabeling of MAC387+, CD79+, and WC1+ cells without connective tissue surrounding the lesion and were associated with less vimentin, Alpha Smooth Muscle Actin (α-SMA), and TGF-β compared with granulomas from adult cattle. Our results suggest that the immune responses in granulomas of cattle naturally infected with M. bovis may be age dependent. This implies that an exacerbated proinflammatory response may be associated with active tuberculosis, producing more necrosis and a lower microbicidal capacity in the granulomas of calves naturally infected with M. bovis.